Contemporary Methods of Treating Children with Autoimmune Nephric Diseases - E. V. Kostyrko; P. V. Shumilov (Педиатрическая фармакология)
The review is dedicated to the analysis of contemporary therapies and efficacy thereof for treating children autoimmune nephric diseases. The authors describe peculiarities of using the conventional therapy in children and discuss alternative treatments using cyclosporine, tacrolimus, budesonide and ursodeoxycholic acid, as well as the need in using the second-line drugs for treating patients with resistant autoimmune nephric diseases. The review touches upon the promising approaches to the treatment of this category of patients.